2020
DOI: 10.3390/app10186430
|View full text |Cite
|
Sign up to set email alerts
|

Explosive Strength Modeling in Children: Trends According to Growth and Prediction Equation

Abstract: Lower limb explosive strength has been widely used to evaluate physical fitness and general health in children. A plethora of studies have scoped the practicality of the standing broad jump (SBJ), though without accounting for body dimensions, which are tremendously affected by growth. This study aimed at modeling SBJ-specific allometric equations, underlying an objectively predictive approach while controlling for maturity offset (MO). A total of 7317 children (8–11 years) were tested for their SBJs; demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…This study provides information about strength status in adolescents: children with an ectomorphic body shape, due to their taller physique and reduced body mass, performed better on the speed-agility and the explosive strength tests, as reported previously [ 36 ]. A linear body shape and engagement in EHS could provide useful clues for talent identification.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This study provides information about strength status in adolescents: children with an ectomorphic body shape, due to their taller physique and reduced body mass, performed better on the speed-agility and the explosive strength tests, as reported previously [ 36 ]. A linear body shape and engagement in EHS could provide useful clues for talent identification.…”
Section: Discussionsupporting
confidence: 71%
“…We may speculate that while late developers have longer legs, more importantly, they have a relatively short upper torso (less upper body mass to raise doing sit-ups). Furthermore, sports coaches need to consider the demands of the modern understanding of sports; fast actions rely on speed and agility [ 36 ], where team sport-specific movements are typically observed in the players with a small body size [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another important consideration is allometric scaling, which may provide greater insight into the effects of physical growth on males and females (Carnevale Pellino et al, 2020). Previously, Carnevale Pellino et al (2020) found that girls outperformed boys in the standing broad jump when allometric modelling was used to normalize performance for anthropometric characteristics, further highlighting the complex effect of growth and maturation on physical performance. Indeed, increases in mass and stature, alongside increases in knee valgus angle (Lloyd & Oliver, 2012), cause different challenges for females, and these might help explain findings in our metaanalysis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may relate to differences in female maturation processes, including decreased neuromuscular control, and associated imbalances in muscle strength and activation patterns (Hopper et al., 2017). However, another important consideration is allometric scaling, which may provide greater insight into the effects of physical growth on males and females (Carnevale Pellino et al., 2020). Previously, Carnevale Pellino et al.…”
Section: Discussionmentioning
confidence: 99%